Сравнительный анализ глубинного строения и сейсмичности Днепровско-Донецкой и Кенийской рифтогенных структур - Трипольский, А.А.; Калюжная, Л.Т.; Трипольская, В.А.; Степаненко, В. М. (Видавничий дім "Академперіодика" НАН України, 2008)
The results of comparative studies of the deep structure and seismicity of the Dnieper-Donets paleorift and the Kenya rift are analyzed. It is established that these structures are characterized by both similar and individual features.